HARNESSING BLOCKCHAIN AND EBPF FOR IMMUTABLE AUDIT OF SYSTEM EVENTS: A TECHNOLOGICAL CONVERGENCE APPROACH - Hlushchenko, Pavlo; Dudykevych, Valerii (Ukrainian Information Security Research Journal, 2024)
The importance of secure and reliable system event auditing has grown significantly in today's complex IT environments, where data integrity and security are paramount. Traditional auditing methods, which rely on centralized systems and are vulnerable to tampering and performance bottlenecks, are no longer sufficient. This article addresses these challenges by proposing a novel framework that combines blockchain and eBPF technologies to create an immutable, transparent, and efficient system for event auditing. The proposed solution leverages eBPF's real-time monitoring capabilities and blockchain's tamper-proof ledger to ensure the integrity and verifiability of audit logs. Through a detailed exploration of the conceptual framework and an analysis of potential challenges and solutions, this approach has proven to be effective in enhancing the reliability and security of system event auditing. The results of this study provide a foundation for future implementations, research and robust solutioning for organizations seeking to improve their auditing processes.